Effects of Deposition Temperature on Structural, Optical Properties and Laser Damage of LaTiO3 Thin Films - Jianchao Li; Wanmin Yang; Junhong Su; Chen Yang (Advances in Condensed Matter Physics)
LaTiO3 films were prepared under various deposition temperatures using electron beam evaporation on Si and fused quartz substrates. The relationship between the deposition temperature and structure and properties of optics was investigated by XPS, XRD, and various optical testing. The results showed that the LaTiO3 film is amorphous when the deposition temperature is below 200°C. The refractive index of LaTiO3 films increases from 1.8302 to 1.9112 at 1064 nm with the rise of deposition temperature. The extinction coefficient of LaTiO3 films is less than 10−6 in the range of 350 to 1700 nm. The laser damage threshold increases at first and then decreases with the increase of deposition temperature. The maximum of the laser damage threshold was 18.18 J/cm2 when the deposition temperature was 150°C. Compared with TiO2 film, the chemical structure and the laser damage threshold of LaTiO3 film are more stable by preparation of electron beam evaporation.